PROGRAM HOME VISIT DAN PENDAMPINGAN BELAJAR PADA PELAKSANAAN PEMBELAJARAN JARAK JAUH DI DESA SUKAMULYA KECAMATAN CIPONGKOR KABUPATEN BANDUNG BARAT - Dindin Sofyan Abdullah (LPPM STAI Darul Falah, 2022)
The implementation of distance learning (online learning) as a result of the covid-19 pandemic has had a significant impact on the field of education. Among the negative impacts that arise are the disruption of the relationship between teachers and students which is one of the conditions for achieving an effective learning and the inability of parents to carry out their roles as educators at home. As a solution of the problems, STAI Darul Falah through “KKN Mandiri” program implemented in Sukamulya, Cipongkor, West Bandung whit the local government and schools around the location has implemented home visit program and students learning assistance. Home visits are carried out to provide assistance and understandings to parents, while learning assistance is carried out to supervise learning activities and assist students in doing various school assignments. This activity includes three stages; the preparation stage, the implementation stage and the evaluation stage. The results of the program are: 1) the distance learning activities become more effective, 2) increasing the quantity and quality of communication between schools and parents.